Latest Advances in Intersphincteric Resection for Low Rectal Cancer - Yifan Xv; Jiajun Fan; Yuan Ding; Yang Hu; Yingjie Hu; Zhengjie Jiang; Qingsong Tao (Gastroenterology Research and Practice)
Background. Intersphincteric resection (ISR) has been a preferable alternative to abdominoperineal resection (APR) for anal preservation in patients with low rectal cancer. Laparoscopic ISR and robotic ISR have been widely used with the proposal of 2 cm or even 1 cm rule of distal free margin and the development of minimally invasive technology. The aim of this review was to describe the newest advancements of ISR. Methods. A comprehensive literature review was performed to identify studies on ISR techniques, preoperative chemoradiotherapy (PCRT), complications, oncological outcomes, and functional outcomes and thereby to summarize relevant information and controversies involved in ISR. Results. Although PCRT is employed to avoid positive circumferential resection margin (CRM) and decrease local recurrence, it tends to engender damage of anorectal function and patients’ quality of life (QoL). Common complications after ISR include anastomotic leakage (AL), anastomotic stricture (AS), urinary retention, fistula, pelvic sepsis, and prolapse. CRM involvement is the most important predictor for local recurrence. Preoperative assessment and particularly rectal endosonography are essential for selecting suitable patients. Anal dysfunction is associated with age, PCRT, location and growth of anastomotic stoma, tumour stage, and resection of internal sphincter. Conclusions. The ISR technique seems feasible for selected patients with low rectal cancer. However, the postoperative QoL as a result of functional disorder should be fully discussed with patients before surgery.